Proceedings 14th IEEE Symposium on Computer-Based Medical Systems. CBMS 2001
DOI: 10.1109/cbms.2001.941770
|View full text |Cite
|
Sign up to set email alerts
|

Optimal scanning, display, and segmentation of the International Labor Organization (ILO) X-ray images set for pneumoconiosis

Abstract: A method for scanning und displa,ving c h i radiogruphs (i-rajo) is presented. The new method irents scanning indeyendeni of display, Lillowing,for niasirniini informulion con lent to be captured during /he scanning process. und then ,for this inforrnaiion io be optiniullv displuyd irsing new fiuiction j o r tna.~iniizing the contrasi vuriotion thrvirghour the inluge. The qirulity of the digirized x-ray images were compared ugainsr the original s-rcrj~.filnis and were jbiind io be vf coniparuble visimlization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Натепер основним визнаним методом діагностики пневмоконіозу є рентгенологічний [11][12][13]. Сьогодні визначені основні та другорядні критерії рентгенологічної діагностики захворювання згідно з Міжнародною класифікацією МОП 2000 року [14].…”
Section: оригінальні статтіunclassified
“…Натепер основним визнаним методом діагностики пневмоконіозу є рентгенологічний [11][12][13]. Сьогодні визначені основні та другорядні критерії рентгенологічної діагностики захворювання згідно з Міжнародною класифікацією МОП 2000 року [14].…”
Section: оригінальні статтіunclassified
“…An AM-FM method for grading chest radiographs according to the ILO standards is presented in [67,68] by Murray et al Related work, by different research groups, can be found in [102][103][104][105][106][107][108]. First, a logarithmic transformation to the images is applied to improve the contrast of the X-Rays [109]. Then, the AM-FM estimates of each X-Ray image is encoded using their histograms as described in the Section 2.4.1 using the tuned bandpass filters and scales showed in Tables 1 and 2.…”
Section: Pneumoconiosis In Chest Radiographsmentioning
confidence: 99%